Lean Approach to Identifying Problems in Outpatient Pharmacy Installations at Simo General Hospital, Boyolali, Indonesia - Setiaji Wisnu Wardana; Rina Herowati; Wiwin Herdwiani (Archives of The Medicine and Case Reports, 2023)
Lean approach is a method used to analyze value-added and non-value-added activities with the aim of minimizing or eliminating the waste that happens in an institution. The purpose of this research is to identify waste and find the root cause of waste that occurred in the outpatient pharmacy installation at the Simo General Hospital. This research method is non-experimental descriptive research with a qualitative descriptive exploratory approach through questionnaires, observation, and in-depth interviews with respondents. The analysis of this research is the observation of the service process flow with value stream mapping, distributing questionnaires, Borda method to search waste critically, 5why interviews to find the root cause of waste criticism and suggestions for solving problems. The results showed that the critical waste that occurred was waste waiting with a percentage value of 23.41%. The root cause of waste waiting is the accumulation of prescription queues at the preparation, dispensing delivery of drugs, and PIO stages due to a lack of pharmaceutical technical personnel. The proposed improvement in waste waiting is to increase the number of pharmacy officers by first calculating the workload.